2004
DOI: 10.1055/s-2004-834807
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Trimers of Chiral Furan Amino Acids

Abstract: Chiral furan amino acids were synthesized as novel peptide building blocks. Cyclooligomerization of these monomers by a single-step process led to the selective formation of chiral C 3 -symmetric cyclic trimers, which were studied for their structures and properties, like anion binding and antimicrobial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 4 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…A plethora of domains such as catalysis, photonics, material science, can also be targeted. [33][34][35][36] We have been particularly interested in synthesizing tubes through controlled stacking of sufficiently rigid ring units 1-4; each unit consisted of a macrolactam [37][38][39][40][41][42][43][44] of C n symmetry (n = 2, 3, 4, Figure 1). [45,46] Owing to the vast potential of such compounds we looked for expedient and efficient syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of domains such as catalysis, photonics, material science, can also be targeted. [33][34][35][36] We have been particularly interested in synthesizing tubes through controlled stacking of sufficiently rigid ring units 1-4; each unit consisted of a macrolactam [37][38][39][40][41][42][43][44] of C n symmetry (n = 2, 3, 4, Figure 1). [45,46] Owing to the vast potential of such compounds we looked for expedient and efficient syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…Our use of this approach complements substantial prior work by others who used an MCO strategy to prepare oligomeric esters and amides. Most notable is the use of activated seco -acids to form macrodiolides (and triolides) and amidations of activated peptidic amino acids to construct the macrocyclic peptides valinomycin and westiellamide. A common feature to these amidation reactions is a five-membered heterocycle, such as a thiazole or oxazole, installed in the peptide backbone. This presumably enhances a conformation more favorable for cyclization.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In further studies, optically active derivatives of H-Faa-OH were synthesized as well as their symmetric optically active macrocyclic trimers 236a−c. 111 The starting materials in this synthesis are chiral N-Boc-amino aldehydes 230a−c derived from the corresponding amino acids and (S)- Calculations showed that in comparison with 226, compounds 236a−c are not planar. 111 The incorporation in the structure of chiral side chains changes the planar geometry of these trimers to the form of a tripod bowl with S-cisorientation of all amide carbonyls and NH bonds directed to the same side.…”
Section: Furans In Macrocyclic Peptide Scaffoldsmentioning
confidence: 99%
“…111 The starting materials in this synthesis are chiral N-Boc-amino aldehydes 230a−c derived from the corresponding amino acids and (S)- Calculations showed that in comparison with 226, compounds 236a−c are not planar. 111 The incorporation in the structure of chiral side chains changes the planar geometry of these trimers to the form of a tripod bowl with S-cisorientation of all amide carbonyls and NH bonds directed to the same side. The torsion angle of HN-Cα-H for both 236a and 236c is ∼175°, and it is ∼180°(trans) for 236b.…”
Section: Furans In Macrocyclic Peptide Scaffoldsmentioning
confidence: 99%